(3GdVYaGA hGdcPCHhf hGdeJQhchf ef CUMGH GdMOjKs - (3CHh YKeGf SYjO Hf YeQh Hf YeGQ GdHQPYj GdMGaX, GdHQPYj,J (B292 (3g` s ((3ESeGYjd Hf YHO Gddg Hf YHO GdeMSf GdCfUGQi GdeUQi s)
(3ChdgG (B:s
(3GdMeO ddg HLejY eMGeOg , hSdGe Ydi YHGOg GdPjf EUWai s
(3BNQgG (B:s
(3EfJgG cJGH CHj YKeGf GdHQPYi ai GdVYaGA hGdeJQhcjf hGdcPGHjf hddg GdMeO s
(3Yf CHi RQYI YHjO Gddg Hf YHO GdcQjes
(3hCHi MGJe eMeO Hf EQOjS GdQGRis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B99s
Keywords: (3GdJGQjNs